The policy network for effectiveness in corporate social responsibility - Ine Mariane (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Research objectives to analyze the effectiveness of policy networks, strategies to face CSR problems in the city of Bandung. This research uses a qualitative approach, with the SWOT analysis method. The results of the study were the effectiveness of policy networks in CSR in Bandung, emphasizing strategy; S-O synchronization of the CSR program with the RPJMD (company program with ISO 26000: 2010 standard), strong regulations from the central, provincial and district/city levels; W-O strategy to strengthen coordination between stakeholders, academics and the community in CSR coordination meetings with related parties; S-T strategy of consolidation, integration, synchronization of company regulations and government programs, strengthening of the CSR Forum, enforcement of regulations on CSR, strengthening of regulations from head office to branch offices; The Regional Government's W-T strategy is to supervise, tighten CSR regulations, synergize communication between governments and companies, use internet technology, socialize and disseminate to related institutions, meetings and summons of CSR-related parties. The effectiveness of the Policy Network in CSR in Bandung City has the opportunity to develop by being obliged by law for companies to implement CSR that cares about environmental conservation, public awareness, regional autonomy, competent parties participate in participatory decision-making processes, democracyin realizing sustainable development.